Plasmodium TatD-Like DNase Antibodies Blocked Parasite Development in the Mosquito Gut - Wang, Wei; Liu, Fei; Jiang, Ning; Lu, Huijun; Yang, Na; Feng, Ying; Sang, Xiaoyu; Cao, Yaming; Chen, Qijun (Frontiers in Microbiology, 2018)
The TatD-like DNase of Plasmodium species has previously been characterized as a conserved antigen that plays an important role in immune evasion. Here, we found that TatD-like DNase is expressed, apart from the erythrocytic stage, throughout the developmental stages of the parasite in the mosquito vector. Antibodies to the molecule significantly blocked parasites development and transition in the mosquito gut. Further, mice immunized with recombinant TatD-like DNase showed significant resistance to parasite challenge. The antigenicity of the TatD-like antigen in combination with various adjuvants, including Freund’s adjuvants, Montanide ISA 51 and 61, Alhydrogel (aluminum hydroxide), and levamisole was investigated. It was found that immunization of the recombinant TatD-like DNase in combination with Montanide ISA 51 induced strong humoral responses that showed significant protection against parasite challenge in a mouse model. The data further support that TatD-like DNase is a functionally important molecule in the whole development cycle of the malaria parasites and a candidate for malaria vaccine development.